Test-retest reliability of EQ-5D-Y best-worst scaling choices of adolescents and adults - Xiong, X; Dalziel, K; Huang, L; Rivero Arias, O (Elsevier, 2022)
Background: There is an increasing interest to obtain adolescents’ own health state valuation preferences and to understand how these differ from adult preferences for the same health state. An important question in health state valuation is whether adolescents can report preferences reliably, yet research remains limited.